A Case of Borderline Erotomania Accompanying Obsessive Compulsive Disorder and Psychogenic Polydipsia: Case Report - Korkmaz, Sevda; Kuloglu, Murat; Bahceci, Bulent; Atmaca, Murad (Ortadogu Ad Pres & Publ Co, 2012)
Borderline erotomania, which is also named violent attachment disorder or nondelusional erotomania is a syndrome that erotomanic behavior pattern is not at delusional level but may be with violence attacks and is characterized with pathologic attachment to opposite sex. Psychogenic polydipsia is a clinical entity emerging without a physiological stimulant and is characterized with drinking too much water. Cases of psychogenic polydipsia accompanied with psychiatric diseases like bipolar disorder, schizophrenia and anorexia nevroza were reported in the literature. However, there is no report on psychogenic polydipsia accompanying borderline erotomania. In this report, a case of borderline erotomania accompanying obsessive compulsive disorder and psychogenic polydipsia was presented. This case may contributed to the assessment of comorbidities with a rare disease.
Obsesif kompülsif bozukluk ve psikojenik polidipsi birlikteli?i olan bir borderline erotomani olgusu
Keywords: Obsessive-compulsive disorder; water intoxication; delusions